ICERI2016 Proceedings 2016
DOI: 10.21125/iceri.2016.1198
|View full text |Cite
|
Sign up to set email alerts
|

Technology Enhanced Informal Learning, Interdisciplinarity, and Cultural Historical Activity Theory

Abstract: This paper explores the role of theory and interdisciplinarity in Technology Enhanced Informal Learning, and the research community. We consider Cultural Historical Activity Theory (CHAT) but we strongly feel that our argument has broader application to the use of theory as part of the intellectual 'self-defence toolkit' that researchers and practitioners in the critical TEL community need to consider if they are to 'resist' the crises arising from educational globalisation. Theory offers us the history, scope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…One key element of this approach is that the network will use creative practices as the ‘shared language’ to facilitate communication between participating researchers. Our recent research (Sclater, 2016; Sclater and Lally, 2016a) had highlighted the need for novel and creative ways to mediate interdisciplinary communications in order to support collaborative working. We have also shown that creative practices can offer a powerful language for such collaborative communication (Lally and Sclater, 2012, 2013; Sclater and Lally, 2013, 2014).…”
Section: Interdisciplinarity – Creativity Immigrants Disciplinary Wmentioning
confidence: 99%
See 1 more Smart Citation
“…One key element of this approach is that the network will use creative practices as the ‘shared language’ to facilitate communication between participating researchers. Our recent research (Sclater, 2016; Sclater and Lally, 2016a) had highlighted the need for novel and creative ways to mediate interdisciplinary communications in order to support collaborative working. We have also shown that creative practices can offer a powerful language for such collaborative communication (Lally and Sclater, 2012, 2013; Sclater and Lally, 2013, 2014).…”
Section: Interdisciplinarity – Creativity Immigrants Disciplinary Wmentioning
confidence: 99%
“…In earlier work (Sclater and Lally, 2017) we commenced the task by looking explicitly at interdisciplinarity in relation to TEL. We reported on the central role of art and design education in bringing creative practices into informal TEL learning communities, and talked with researchers who were members of an interdisciplinary TEL team in Scotland (Sclater and Lally, 2016a: 865).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many frameworks, checklists, and evaluation methodologies have emerged to address ethical and moral considerations of LA system development and interventions. These include, among others, the socio-critical ethical framework (Slade & Prinsloo, 2013), a set of design guidelines (Pardo & Siemens, 2014), the DELICATE ethics checklist (Drachsler & Greller, 2016), JICS's code of practice (Sclater & Lally, 2016), the SHEILA (Supporting Higher Education to Integrate Learning Analytics) policy framework (Tsai et al, 2018), and the more recent global guidelines for the ethics of LA (Slade & Tait, 2019). As LA systems evolve and become more technically sophisticated, including recent developments in AI (Buckingham Shum & Luckin, 2019), their further design and use in education contexts bring new questions into focus.…”
Section: Introductionmentioning
confidence: 99%